THEORETICAL ENCAPSULATION OF FLUOROURACIL (5-FU) ANTI-CANCER CHEMOTHERAPY DRUG INTO CARBON NANOTUBES (CNT) AND BORON NITRIDE NANOTUBES (BNNT) - Dehaghani, Maryam Zarghami; Yousef, Farrokh; Sajadi, S. Mohammad; Munir, Muhammad Tajammal; Abida, Otman; Habibzadeh, Sajjad; Mashhadzadeh, Amin Hamed; Rabiee, Navid; Mostafavi, Ebrahim; Saeb, Mohammad Reza (Molecules, 2021)
Chemotherapy with anti-cancer drugs is considered the most common approach for killing cancer cells in the human body. However, some barriers such as toxicity and side effects would limit its usage. In this regard, nano-based drug delivery systems have emerged as cost-effective and efficient for sustained and targeted drug delivery. Nanotubes such as carbon nanotubes (CNT) and boron nitride nanotubes (BNNT) are promising nanocarriers that provide the cargo with a large inner volume for encapsulation. However, understanding the insertion process of the anti-cancer drugs into the nanotubes and demonstrating drug-nanotube interactions starts with theoretical analysis. Methods: First, interactions parameters of the atoms of 5-FU were quantified from the DREIDING force field. Second, the storage capacity of BNNT (8,8) was simulated to count the number of drugs 5-FU encapsulated inside the cavity of the nanotubes. In terms of the encapsulation process of the one drug 5-FU into nanotubes, it was clarified that the drug 5-FU was more rapidly adsorbed into the cavity of the BNNT compared with the CNT due to the higher van der Waals (vdW) interaction energy between the drug and the BNNT. Results: The obtained values of free energy confirmed that the encapsulation process of the drug inside the CNT and BNNT occurred spontaneously with the free energies of −14 and −25 kcal·mol−1 , respectively. Discussion: However, the lower value of the free energy in the system containing the BNNT unraveled more stability of the encapsulated drug inside the cavity of the BNNT comparing the system having CNT. The encapsulation of Fluorouracil (5-FU) anti-cancer chemotherapy drug (commercial name: Adrucil®) into CNT (8,8) and BNNT (8,8) with the length of 20 Å in an aqueous solution was discussed herein applying molecular dynamics (MD) simulation
Keywords: drug delivery; Type of access: Open Access; carbon nanotubes; boron nitride nanotubes; chemotherapy; drug delivery system; molecular dynamics; DREIDING force field; anti-cancer drug; Fluorouracil